Case report: Pathology, antimicrobial resistance, and molecular characterization of bovine abortion cases caused by Nocardia farcinica in Korean native cattle - Kim, Eun-Mi; Yun, Chi Sun; Bae, You-Chan; Lee, Hyunkyoung; Moon, Bo-Youn; Lee, Kichan; Jeoung, Hye-Young; Ku, Bok-Kyung; Kim, Jongho (Frontiers in Veterinary Science, 2024)
Introduction: Nocardia farcinica is an opportunistic bacterium that causes bovine mastitis and pulmonary, cutaneous, and central nervous system infections in humans. Bovine abortion caused by N. farcinica has been sporadically reported. The purpose of this study was to analyze the pathological findings of bovine abortions caused by N. farcinica in the Republic of Korea and determine the antimicrobial resistance and genotypical characteristics of N. farcinica isolates.Case presentation: Three cases of bovine abortions were submitted to the Animal and Plant Quarantine Agency for differential diagnosis. Grossly, one fetus showed severe lung consolidation following palpation of the entire lobes. Histologically, necrotizing granulomatous interstitial pneumonia was observed in all fetuses; a fetus with a gross lesion demonstrated necrotizing lymphadenitis in the mesenteric lymph nodes and necrotizing dermatitis in the ear. N. farcinica isolates were isolated from the abomasal contents and lungs of all fetuses. Finally, two cases were diagnosed as abortions due to N. farcinica, and one was diagnosed as an N. farcinica abortion coinfected with bovine viral diarrhea virus. According to the multilocus sequence analysis, all isolates were identified as N. farcinica and were determined to be genetically related to isolates from humans. Two N. farcinica isolates were resistant to trimethoprim-sulfamethoxazole, which is recommended as the first treatment for human nocardial infections. Conclusion: This is the first pathological report of bovine abortion caused by N. farcinica in the Republic of Korea. Further studies are needed to phenotypically and genotypically characterize N. farcinica isolates with various sources and continuously monitor antimicrobial resistance patterns. * NT, Not determined ** Except for Bov-fet-2 MIC, minimal inhibitory concentration